Chapter Posidonia oceanica monitoring system on the coast of Aegean Sea of Turkey - Çalik, Hayati (Proceedings e report, 2020)
Seagrass monitoring is a basic tool for measuring the condition of meadows in parallel to the environmental conditions. Posidonia oceanica meadows are very sensitive to anthropogenic effects. In the present study, two monitoring stations of Posidonia oceanica meadows were established on the Aegean coasts of Turkey in the years 2018 and 2019, at 26 m depth in Ildır Bay (İzmir, Turkey), and at 33 m depth in Kara Ada (İzmir, Turkey). The P. oceanica meadows upper and lower limits were defined by balisage systems. In the laboratory, lepidochronological, morphometric, and phenological parameters were also studied.